PELATIHAN PEMBUATAN TELUR ASIN DI DESA POOWO BARAT KECAMATAN KABILA KABUPATEN BONE BOLANGO - Umbang Arif Rokhayati (PARADIGMA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this service is to provide training in making salted eggs and improve skills in making salted eggs. The targets of this activity are: 1) PKK mothers can process salted eggs, 2) There will be an increase in the economy, 3) Increase the knowledge and skills of the community. The method of this activity is the method of socialization and lectures. The results achieved were increasing knowledge and providing skills to PKK women in Poowo Village, Kabila District to make an animal-based food product with egg-based ingredients which has become the main and staple part of the community's food ingredients.